Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1182/blood.2022016170
|View full text |Cite
|
Sign up to set email alerts
|

MRD in multiple myeloma: does CR really matter?

Abstract: Multiple myeloma embodies the paradigm of the deepest the response the longer the survival. However, there are conflicting results between the achievement of complete remission and MRD negativity, because some patients with persistent M-protein have nonetheless undetectable MRD. We reviewed the frequency of this discordancy and the outcome of these patients. We spotlighted possible explanations and consequences of conflicting response criteria, and suggest that MRD should be assessed in patients achieving very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…NGF, which relies on antibodies targeting cell surface proteins, and NGS, which identifies genetic mutations, focus on distinct biological markers [ 36 , 37 ]. This divergence in methodological focus can lead to scenarios where MRD is detectable by one technique but remains undetected by the other, reflecting the distinct detection capabilities inherent to each method [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…NGF, which relies on antibodies targeting cell surface proteins, and NGS, which identifies genetic mutations, focus on distinct biological markers [ 36 , 37 ]. This divergence in methodological focus can lead to scenarios where MRD is detectable by one technique but remains undetected by the other, reflecting the distinct detection capabilities inherent to each method [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies did not definitively clarify neither what the ideal threshold of sensitivity is, the optimal timing for MRD assessment, nor if achievement of MRD negativity has the same value in SR, HR or ultra-high-risk patients, given that the MASTER trial [ 130 ] showed different outcomes in these groups of patients despite MRD negativity. Moreover, the discordance between the achievement of CR according to IMWG criteria [ 120 ] and MRD negativity [ 241 ] should be better explained. Another unresolved issue is in regard to the minimal duration of sustained MRD negativity required to be a strong prognostic factor since, as reported in patients enrolled in the MAIA and ALCYONE trials [ 124 ], PFS was not the same when sustained MRD lasted less or more than 12 months.…”
Section: Discussion and Expert Opinionmentioning
confidence: 99%
“…It is now well established that bone marrow based MRD evaluation provides better prognostic performance than SPEP/IFE [56]. Intriguingly, there are reports indicating that among patients with MRD-negativity, achievement of complete response based on conventional IMWG criteria (i.e., negative by SPEP/IFE) does not affect prognosis [57], raising a concern about false-positive SPEP/IFE results. M-protein detection by mass spectrometry (MS) has a potential to address both aforementioned shortcomings of the classical method.…”
Section: Mass Spectrometrymentioning
confidence: 99%